2021
DOI: 10.3389/fphys.2020.469499
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Exercise in Different Postures on Handgrip Strength in Healthy Women: A Cross-Over Study

Abstract: ObjectiveTo compare the effect of Whole-Body Vibration Exercise (WBVE) applied in push-up modified and half-squat positions, on handgrip strength (HS) and on the electromyography registry (EMGrms) of the flexor digitorum superficialis muscle (FDSM) of the dominant hand.MethodsNineteen healthy women (age 23.40 ± 4.03 years, bodyweight: 58.89 ± 9.87 kg), performed in a randomized order five different tests: (S1) Control; (S2) Push-up modified; (S3) Push-up placebo; (S4); Half-squatting; (S5) Half-squatting place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Regarding the changes and consequent neuromuscular modifications of the hands, to our knowledge, there are no studies that have reported this in RA population. However, Krol et al [ 34 ] and other researches demonstrated an increase in the neuromuscular efficiency and concluded that vibration exercise can be useful to stimulate the neuromuscular system in healthy population [ 14 , 19 , 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the changes and consequent neuromuscular modifications of the hands, to our knowledge, there are no studies that have reported this in RA population. However, Krol et al [ 34 ] and other researches demonstrated an increase in the neuromuscular efficiency and concluded that vibration exercise can be useful to stimulate the neuromuscular system in healthy population [ 14 , 19 , 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the stimulus duration varied from 10.5 minutes to 15 minutes intermittently [ 13 , 35 , 36 ]. Nevertheless, the current WBV parameters (frequency: 45 Hz; amplitude: 2 mm, acceleration: 159.73 m·s −2 ) of 5 minutes continuous WBV were selected based on previous research [ 19 , 20 , 22 , 23 ]. Additionally, all participants adhered to the 5-minute protocol and successfully completed the vibration without discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among our previous studies, a cross-sectional study demonstrated a negative correlation between lumbar neuromuscular function and pain in NSLBP patients [19] and a meta-analysis verified that compared with general exercise, core stability exercise is more effective in alleviating pain and increasing the lumbar muscular functional status in patients with low back pain in the short term [20]. As a new type of core stability exercise in pain relief [21], whole-body vibration (WBV) exercise requires the individual to perform static or steadily controlled exercises on an oscillating platform [22,23] and becomes a credible procedure for enhancing muscular performance [24][25][26][27]. A number of vibration-related research studies have suggested that these positive acute effects are attributed to neural adaptation, containing increased facilitated stretch reflex and muscle activation [23,28,29].…”
Section: Introductionmentioning
confidence: 99%